2017
DOI: 10.1080/1351847x.2017.1371622
|View full text |Cite
|
Sign up to set email alerts
|

Gender role asymmetry and stock market participation – evidence from four European household surveys

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 82 publications
3
14
1
2
Order By: Relevance
“…This research was in accordance with research [11] which showed that gender did not have any effect on the interest in investing. On the other hand, this research was not in line with research [7,16]. The results also show that gender has not been consistently shown to influence financial behavior.…”
Section: Based Oncontrasting
confidence: 92%
See 1 more Smart Citation
“…This research was in accordance with research [11] which showed that gender did not have any effect on the interest in investing. On the other hand, this research was not in line with research [7,16]. The results also show that gender has not been consistently shown to influence financial behavior.…”
Section: Based Oncontrasting
confidence: 92%
“…Constant value as much as 16.497 stated that if independent variables were considered constant, then average students' interest to invest in the stock market was as much as 16.497. Aside from that, the regression equation above showed the effect of each independent variable towards the dependent variable, which could be seen from sig.…”
Section: Resultsmentioning
confidence: 99%
“…There are many factors affecting the scale and the range of participation in particular forms of investing. The results of much research confirm the impact of many different socio-demographic factors, for instance: age, education, income, wealth, employment status and occupation, stages in the life cycle and marital status (Aren & Aydemir, 2015;Barasinska & Schäfer, 2018;Kumari, Satya, & Kritika, 2018). The conducted research also confirms that an investment objective and an asset familiarity play a vital role in the choice of elements of the investment portfolio (Seetharaman, Niranjan, Patwa, & Kejriwal, 2017).…”
Section: Literature Reviewsupporting
confidence: 59%
“…Considering that research devoted strictly to gender differences in financial behaviour is scanty, some light on this issue may be shed by studies on risk aversion. As indicated by Barasinska and Schäfer (2018), risk aversion is the most frequently investigated issue in the research strand that focuses on the financial choices of women and men. Many studies showed that women report being less risk-taking than their male peers or that they behave in a more risk-averse way (Baeckstrom, Marsh, & Silvester, 2019;Beckmann & Menkhoff, 2008;Charness & Gneezy, 2012;Powell & Ansic, 1997;Weber, Weber, & Nosić, 2013).…”
Section: Empirical Findings On the Gender Gap In Financial Behaviourmentioning
confidence: 99%
“…Large-scale OECD studies (OECD, 2016(OECD, , 2020 identified relatively few differences between women and men in this respect. Even risk aversion research, which has a particularly long tradition, has not clearly confirmed differences between women and men in this regard (see a review provided by Barasinska and Schäfer 2018).…”
Section: Introductionmentioning
confidence: 99%